2022
DOI: 10.1111/bph.15797
|View full text |Cite
|
Sign up to set email alerts
|

Linking drug and food addiction via compulsive appetite

Abstract: Background and Purpose ‘Food addiction’ is the subject of intense public and research interest. However, this nosology based on neurobehavioural similarities among obese individuals, patients with eating disorders and those with substance use disorders (drug addiction) remains controversial. We thus sought to determine which aspects of disordered eating are causally linked to preclinical models of drug addiction. We hypothesized that extensive drug histories, known to cause addiction‐like brain changes and dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…Investigation into the neurobiological mechanisms involved in compulsive behaviour driven by drugs and obesogenic diets using animal models found overlapping neuroadaptations [53]. In humans, neuroimaging studies have demonstrated that both food and drugs of abuse can stimulate dopamine-based reward pathways [54], providing support that FA may operate similarly to substance use disorders.…”
Section: Cravingmentioning
confidence: 99%
“…Investigation into the neurobiological mechanisms involved in compulsive behaviour driven by drugs and obesogenic diets using animal models found overlapping neuroadaptations [53]. In humans, neuroimaging studies have demonstrated that both food and drugs of abuse can stimulate dopamine-based reward pathways [54], providing support that FA may operate similarly to substance use disorders.…”
Section: Cravingmentioning
confidence: 99%
“…It has been suggested that increases in mesolimbic dopamine may suppress food consumption, similar to what is seen following administration of the dopamine type-2 receptor agonist, bromocriptine (Thanos et al, 2011). However, following acute cocaine-induced appetite suppression, rats display increased motivation for high-calorie food which may lead to “binge eating” in cocaine-experienced rats (Laque et al, 2022). Clinical and preclinical work suggests that subjects with a history of cocaine use consume more calories and more high-fat food, but they do not gain more weight than non-cocaine users (Ersche et al, 2013; Bane et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Alongside their apparent reliance on aberrant dopaminergic mechanisms, the compulsive nature of ICDs, which is not without similarities with that of substance use disorders [11][12][13][14][15][16][17][18], has led to their conceptualization as a form of behavioral addiction [19][20][21]. Similarly to psychostimulant use disorder, the vulnerability to develop ICDs has been shown to be associated with a high impulsivity trait [14,17,[21][22][23][24], which is characterized by a tendency to act prematurely, without forethought or concerns for adverse upcoming consequences [25].…”
Section: Introductionmentioning
confidence: 99%